Somatotopic Mapping of Piano Fingering Errors in Sensorimotor Experts: TMS Studies in Pianists and Visually Trained Musically Naïves. (12th October 2012) - Candidi, Matteo; Maria Sacheli, Lucia; Mega, Ilaria; Aglioti, Salvatore Maria
Abstract : Virtuosic musical performance requires fine sensorimotor skills and high predictive control of the fast finger movements that produce the intended sounds, and cannot be corrected once the notes have been played. The anticipatory nature of motor control in experts explains why musical performance is barely affected by auditory feedback. Using single-pulse transcranial magnetic stimulation, we provide evidence that, in expert pianists (Experiment 1), the observation of a mute piano fingering error induces 1) a time-locked facilitation of hand corticospinal representation which occurred 300 and 700 ms but not 100 ms after error onset, and 2) a somatotopic corticospinal facilitation of the very same finger that commits the error. In a second experiment, we show that no corticospinal modulation is found in non-pianist naïve individuals who were experimentally trained to visually detect the observed fingering errors (Experiment 2). This is the first evidence showing that the refined somatosensory and motor skills of musicians exceed the domain of individual motor control and may provide the brain with fine anticipatory, simulative error monitoring systems for the evaluation of others' movements.